The Magnetic Resonance Imaging in Active Surveillance (MRIAS) Trial: Use of Baseline Multiparametric Magnetic Resonance Imaging and Saturation Biopsy to Reduce the Frequency of Surveillance Prostate Biopsies - Amin, Amer; Scheltema, Matthijs J.; Shnier, Ron; Blazevski, Alexandar; Moses, Daniel; Cusick, Thomas; Siriwardena, Amila; Yuen, Brian; van Leeuwen, Pim J.; Haynes, Anne Maree; Matthews, Jayne; Brenner, Phillip; et al. (The Journal of urology, 2020)
Prospective studies are lacking in assessing the diagnostic utility of serial multiparametric magnetic resonance imaging to predict biopsy proven progression to clinically significant prostate cancer in men on active surveillance, as well as the oncologic safety of baseline magnetic resonance imaging and saturation diagnostic biopsy in replacing early confirmatory biopsy during active surveillance. A total of 172 men were enrolled in this single arm prospective trial. Men with cT2 or lower histologically proven prostate cancer (Gleason 3+3=6 or Gleason 3+4=7 with 10% or less Gleason pattern 4 overall and less than 2 cores Gleason pattern 4) eligible for surveillance were included in the study. Men underwent baseline multiparametric magnetic resonance imaging and saturation biopsy followed by serial annual multiparametric magnetic resonance imaging until a 3-year end point per protocol saturation biopsy. The standardized 1-year confirmatory biopsy was omitted and biopsies during the protocol were triggered based on new abnormalities on multiparametric magnetic resonance imaging and prostate specific antigen density. We report the prespecified interim analysis of the first 100 men at 3 years. At baseline the median age was 64.5 (IQR 57.25-69) years, prostate specific antigen was 4.7 ng/ml (IQR 3.4-6.6), 91% had Gleason 3+3=6 prostate cancer and multiparametric magnetic resonance imaging was negative (Prostate Imaging Reporting and Data System 1/2/3) in 87% of men. Within 3 years 21% experienced pathological progression. The positive predictive value, negative predictive value, sensitivity and specificity for detection of clinically significant prostate cancer by surveillance multiparametric magnetic resonance imaging was 45%, 89%, 61% and 80%, respectively. Positive surveillance magnetic resonance imaging (p=0.002) and prostate specific antigen density greater than 0.2 ng/ml (p=0.042) had significant predictive value for clinically significant prostate cancer. Our novel active surveillance protocol incorporating multiparametric magnetic resonance imaging detected most cases of disease progression and may enable confirmatory biopsy to be deferred, but should not replace 3-year surveillance biopsy altogether due to occasional magnetic resonance imaging invisible tumors.